The Effect of Shopping Orientation, Product Attributes, and Electronic Word of Mouth (E-WOM) on online Purchase Intent in The Marketplace - Sihombing, Joel Chandra; Bangsawan, Satria; Mahrinasari, M.S. (Publikasi Indonesia, 2023)
Each individual has a different shopping orientation which is shown through opinions, desires, and individual activities when shopping. Currently, individual understanding of shopping orientation is the ease of shopping. The convenience of this shopping can be obtained through online shopping marketplaces. Some of the attributes that exist in the online marketplace as a shopping place used by consumers are having a variety of choices in payment methods, ease of use, data security factors are also important including security in transactions, product guarantees, speed of delivery and related shipping fee promos offered, this is often a consideration for consumers to buy a product on an online marketplace. Online marketplace providers such as Shopee, Tokopedia, Bukalapak, and others each provide comment column features such as product reviews and product discussions to assist customers in making purchases. The purpose of this study was to determine the effect of shopping orientation, product attributes and electronic word of mouth partially on online purchase intentions in marketplaces using multiple linear regression analysis. The research population was Indonesian people who had purchased online marketplaces with a sample of 270 respondents using the purposive sampling method, and then processed with the help of SPSS 25 statistical software. The results showed that from multiple linear regression analysis and testing the shopping orientation hypothesis, product attributes and electronic word of mouth positively and significantly influences purchase intention.